The Role of the Oversight Mechanism in fostering Ethical Work Climates in Municipal Local Governments - Makanga, Christopher Neil (Jurnal Karya Abdi Masyarakat, 2026)
This paper sought to investigate the relationship between oversight mechanisms and ethical work climate using a quantitative research approach. Data were collected through a pre-coded structured questionnaire to obtain respondents’ views on the study variables and were analyzed using SPSS and PLS-SEM to examine the relationships among the variables. The findings confirmed the main hypothesis that oversight mechanisms have a positive relationship with ethical work climate and further validated agency theory, highlighting the essential role of independent oversight agencies in shaping managers’ ethical behavior within their work environments. The originality of this study lies in its investigation of the combined roles of four oversight mechanism functions internal audit, audit committees, external audit, and parliamentary public accountability committees in influencing the ethical work climate of municipal local governments in a developing country context.